Initiation of Liver Transplant in Nepal: A Milestone. (14th October 2022) - Shrestha, Pukar Chandra; Joshi, Neeraj; Gurubacharya, Dipesh Lal; Devbhandari, Mohan; Rai, Aarati; Bhandari, Tika Ram; Shrestha, Prakriti; Paneru, Pragya; Gupta, Subhash; Kwon, Choon Hyuck David
Abstract : Background . The incidence of chronic liver disease is increasing in the Nepalese population. Liver transplantation (LT) is the best option for patients with end-stage liver disease (ESLD). Nepal's first liver transplant was performed in 2016 in an international collaborative effort at Shahid Dharmabhakta National Transplant Centre (SDNTC), Bhaktapur, Nepal. We aim to report details of the first five patients who had undergone liver transplantation in SDNTC before the beginning of the COVID-19 outbreak in the history of transplantation in Nepal. Method . A descriptive analysis of the clinical data of five adult recipients of liver transplantation at SDNTC was done. We described the patient's demographics, length of stay, and survival of all the first five patients who had undergone four living donor liver transplantations and one brain-dead donor liver transplantation in SDNTC before the beginning of the COVID-19 outbreak. Results . Recipients were between 36 and 63 years old. The recipients of the four live donor liver transplants (LDLT) and one brain-dead donor liver transplant (DDLT) had alcoholic liver disease and cryptogenic liver disease, leading to end-stage liver disease. The model for end-stage liver disease (MELD) scores ranged from 23 to 34. Out of five, four recipients and four donors are doing well and relishing the prospect of a normal life, while the recipient of a brain-dead donor liver transplant passed away due to postoperative primary graft failure. Conclusion . Despite the small number of liver transplants that have been done, the success of these has created confidence in a sustainable liver transplantation program in Nepal.